2013
DOI: 10.1002/cbic.201300372
|View full text |Cite
|
Sign up to set email alerts
|

Geranylation of Cyclic Dipeptides by the Dimethylallyl Transferase AnaPT Resulting in a Shift of Prenylation Position on the Indole Ring

Abstract: The dimethylallyl transferase AnaPT from Neosartorya fischeri is involved in the biosynthesis of acetylaszonalenin and catalyses the regioselective and stereospecific C3α-prenylation of (R)-benzodiazepinedione in the presence of dimethylallyl diphosphate. This enzyme also converts several tryptophan-containing cyclic dipeptides to C3α-prenylated indolines. In this study, we demonstrate the geranylation of (R)-benzodiazepinedione and five other cyclic dipeptides by AnaPT in the presence of geranyl diphosphate (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
25
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 21 publications
(25 citation statements)
references
References 30 publications
0
25
0
Order By: Relevance
“…[9,11,13,15] In contrast, they show high promiscuity for the aromatic substrate and accept a large number of tryptophan derivatives. [9,11,16,17] FgaPT2 and 7-DMATS even used hydroxynaphthalenes as prenyl acceptors; [18] these are natural substrates of prenyltransferases of the CloQ/NphB group, from both bacteria and fungi.…”
Section: Introductionmentioning
confidence: 89%
See 1 more Smart Citation
“…[9,11,13,15] In contrast, they show high promiscuity for the aromatic substrate and accept a large number of tryptophan derivatives. [9,11,16,17] FgaPT2 and 7-DMATS even used hydroxynaphthalenes as prenyl acceptors; [18] these are natural substrates of prenyltransferases of the CloQ/NphB group, from both bacteria and fungi.…”
Section: Introductionmentioning
confidence: 89%
“…Detailed inspection of the 1 H NMR spectra revealed signals for a regular geranyl residue attached at a C atom. [15] The chemical Acceptance of dihydroxynaphthalenes by 6-DMATS Sa and C-prenylation on the unsubstituted benzene ring…”
Section: Confirmation Of the Prenylation Position Of The Enzyme Productsmentioning
confidence: 99%
“…23 Therefore, 1a−9a were incubated with AnaPT in the presence of GPP. HPLC analysis revealed that these compounds were also accepted by AnaPT in the presence of GPP.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
“…Indeed, GPP can be used by AnaPT from N. fischeri for geranylation of (R)-benzodiazepinedione (cyclo-L-Trp-Ant) and five other cyclic dipeptides. C6-and C7-geranylated derivatives were identified as enzyme products (Table 8) (Pockrandt and Li 2013). Obviously, the regioselectivity of the prenyl transfer reaction was reduced in the presence of the long chain donor.…”
Section: Acceptance Of Gpp and Fpp By The Dmats Enzymesmentioning
confidence: 99%
“…It has shown that the double bond The data are adopted from publication for AnaPT (10.1 μM, 6 h) (Zhou et al 2015) The data are adopted from publication for AnaPT (4.0 μM, 16 h) (Pockrandt and Li 2013) n.d. not detected at the ß-position to pyrophosphate is essential for an acceptance by these enzymes. One methyl group can be deleted as in the case of MAPP or shifted to the δ-position as in the case of 2-pentenyl-PP .…”
Section: Acceptance Of Unnatural Dmapp Analogs By the Dmats Enzymesmentioning
confidence: 99%